Analisis Konflik Agraria di Kalimantan Timur: Studi Kasus Sengketa Lahan Antara Masyarakat Adat dan Perusahaan Tambang - Prasetya, Noviar Haikal; Zuffran, Fauzie; Murtada, Fathur Sultan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze agrarian conflicts in East Kalimantan, focusing on land disputes between indigenous communities and mining companies. Agrarian conflicts in this region are often caused by differing interests between communities defending their customary land rights and mining companies seeking to exploit natural resources. This research uses a qualitative approach with a case study method to deeply explore the dynamics of the conflict and its impacts on both parties. Data were collected through in-depth interviews with representatives of indigenous communities, company officials, and local government, and analyzed using thematic analysis techniques. The results show that these agrarian conflicts are triggered by unclear land rights boundaries, lack of socialization and community participation in the licensing process, and government policies that tend to support natural resource exploitation. The impact of this conflict is highly detrimental to indigenous communities, both in terms of losing their customary lands, which are their sources of livelihood, and environmental damage that threatens their sustainability. This study recommends a review of agrarian policies, increased participation of indigenous communities in decision-making processes, and conflict resolution through dialogue involving all related parties. Thus, it is expected that fair and sustainable solutions can be created for all parties involved in agrarian conflicts in East Kalimantan.